IN THE LIGHT OF ADOPTION THEORIES: WHY DO AGRICULTURAL EXTENSION AGENTS USE SOCIAL MEDIA? - Tham-Agyekum, Enoch Kwame; Jones, Ebenezer Osei; Bakang, John-Eudes Andivi; Asiedu, Prince; Aidoo, Danley Colecraft; Mensah, Emmanuel Anobir (Socio-Economics/Agribusiness Department, 2023)
This study highlights a significant gap between theoretical understanding and the actual use of social media tools by agricultural extension agents (AEAs). A quantitative study was undertaken to give clear understanding on how various theoretical perspectives in the area of adoption of social media play out in reality among the agricultural extension agents. A sample size of 418 AEAs in the Eastern Region, Ghana were selected using the snowballing sampling technique. The following constructs were rated highest by the respondents; observability, (innovation diffusion theory), continuance intention (theory of task-technology fit), perceived usefulness of social media (theory of reasoned action, theory of planned behaviour, theory of acceptance model) and performance expectancy (unified theory of acceptance and use of technology). Majority of the AEAs highly use social media. High cost of repair of devices, high charges by network providers and lack of knowledge of the best social media use were perceived as substantial challenges. The results show that extension agents must be encouraged to leverage social media platforms to provide personalised support, answer farmers' queries, and offer guidance, leading to better adoption of recommended agricultural practices.